Digitization of the Traditional Karo Wedding Event through Virtual Tour - Gladiola Naomi Pasaribu; Herlina Jasa Putri Harahap (Syntax Corporation Indonesia, 2025)
This research explores the digitization of the traditional Karo wedding event through the implementation of a virtual tour. The study aims to preserve and promote Karo cultural heritage by utilizing digital technology, allowing a broader audience to experience the rich traditions of Karo weddings remotely. By leveraging virtual reality and immersive digital tools, this research analyzes the potential of virtual tours to both educate and engage users, fostering a deeper understanding of cultural values. The findings suggest that the digitization process can enhance cultural preservation efforts and provide new opportunities for global exposure while maintaining the authenticity of the traditional event.